Determination and Statistical Analysis of Effective Watermarking Application among Varied Medical Images - Ayuba, Shehu; Usman, Babawuro (IJRDO -Journal of Computer Science Engineering, 2016)
As security is very crucial in almost every sector of services nowadays, watermarking is moreor less an important mechanism in securing vital information such as medical images. Watermarking aimed at providing secure medical images through integrity verification, such thatunauthorized person cannot be able to modify it. In a bid to find a secured watermarkingtechnique which prevents a medical image from degradation, this research explores amechanism known as Hybrid Transformed Watermarking. Two mechanisms are employedthat include Discreet Cosine Transform (DCT) and Discreet Wavelet Transform (DWT). Thetwo techniques were combined to transform a medical image with the intent of providingauthenticity and integrity verification, the final result was an efficient watermarked imaged.